2019
DOI: 10.1080/21870764.2019.1658339
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of porous ceramic membranes from Sayong ball clay

Abstract: A porous ceramic membrane for the nano-filtration range was fabricated from a mixture of ball clay and starch. Sayong ball clay powders were mixed with starch as a pore former and compacted under a pressure of 200 MPa. The mixture was sintered at temperatures ranging from 900°C to 1200°C. It was found that the porous structure and crystalline phase of the sintered membrane were greatly dependent on the sintering temperature. The membranes exhibited bulk density varying from 1.5 g/cm 3 to 1.9 g/cm 3 , an appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…8a and 8b). Increasing the pressure increases indeed the convective driving force across the membrane support (Mohamed Bazin et al, 2019). In addition, the permeability tests showed that the flow densities obtained with deionized water (Fig.…”
Section: Permeability Of the Selected Support Sn1510mentioning
confidence: 82%
“…8a and 8b). Increasing the pressure increases indeed the convective driving force across the membrane support (Mohamed Bazin et al, 2019). In addition, the permeability tests showed that the flow densities obtained with deionized water (Fig.…”
Section: Permeability Of the Selected Support Sn1510mentioning
confidence: 82%
“…Figure 14 illustrates the obtained results. It is possible to observe that the increases in flux are related to changes in the pressure [52] with a stable flux that was reached after a few minutes. Moreover, a flux rate of 270 lh −1 m −2 at 0.6 bar pressure, which increases to 580 lh −1 m −2 at 1.4 bar, was also measured.…”
Section: Membranes Characterizationmentioning
confidence: 99%
“…It is a mineral compound of hydrated aluminum silicates and metal oxides, namely, MgO and Fe 3 O 4 ( Figure ). [ 33 ] The application of this abundant and low‐cost material can resolve the issue of the cost of the ceramics. Furthermore, the chemical and physical features of clays can change during firing which can be effective for water purification.…”
Section: Nature‐inspired‐based Ceramicsmentioning
confidence: 99%